Ocular biometry in the adult population in rural central China: a population-based, cross-sectional study - Fu, Ting (Int J Ophthalmol, 2015)
AIM: To describe the distribution and determinants of ocular biometric parameters and to ascertain the relative importance of these determinants in a large population of adults in rural central China. METHODS: A population-based, cross-sectional study performed in rural central China included 1721 participants aged 40 or more years. Ocular biometrical parameters including axial length (AL), anterior chamber depth (ACD), radius of corneal curvature (K) and horizontal corneal diameter [white-to-white (WTW) distance] were measured using non-contact partial coherence interferometry [intraocular lens (IOL)-Master]. RESULTS: Ocular biometric data on 1721 participants with a average age of 57.0±8.7y were analyzed at last. The general mean AL, ACD, mean corneal curvature radius (MCR), WTW were 22.80±1.12, 2.96±0.36, 7.56±0.26 and 11.75±0.40 mm, respectively. The mean values of each parameter in 40 to 49, 50 to 59, 60 to 69, and 70 to 91 years age groups were as follows: AL, 22.77±0.87, 22.76±1.06, 22.89±1.41, 22.92±0.80 mm; ACD, 3.10±0.32, 2.98±0.34, 2.86±0.36, 2.77±0.35 mm; MCR, 7.58±0.25, 7.54±0.26, 7.55±0.26, 7.49±0.28 mm; WTW, 11.79±0.38, 11.75±0.40, 11.72±0.41, 11.67±0.41 mm. The AL, ACD, MCR and WTW were correlated with age and the AL was correlated with height and weight. CONCLUSION: Our findings can serve as an important normative reference for multiple purposes and may help to improve the quality of rural eye care.